Transverse colon adenocarcinoma mimicking complicated diverticulitis with abscess: a case report and review of literature - Alsofyani, Talal M.; Alsherbi, Raghad K.; Althobaiti, Hanan S.; Alhemaidi, Fahad M. (International Surgery Journal, 2026)
Colorectal cancer (CRC) is one of the most common cancers leading to death and illness globally. In cases of complicated diverticulitis with abscess, the usual course of action is to manage the condition with antibiotics and drainage. However, Inflammatory diverticular disease may have a similar clinical and imaging presentation to CRC, leading to a diagnostic dilemma. This study presents a case of a 68-year-old male with acute abdominal pain and a non-contrast computed tomography (CT) scan showed distal transverse colon diverticulitis with a 6.1×6.5 cm abscess. He was treated with IV antibiotics and IR-guided percutaneous drainage, but developed a persistent purulent discharge at the drain site, followed by hematochezia. A contrast-enhanced CT scan showed persistent thickening of the colonic wall and a track from the collection to the skin. A subtotal colectomy with loop ileostomy was done. The histopathology showed a perforated, moderately differentiated transverse colon adenocarcinoma (pT4aN0M0; stage IIB). To conclude, the lack of improvement after drainage or the development of a tract/fistula should trigger an urgent reassessment for an occult malignancy and control of the source.